Sequence and settlement at the rural farm of Blaauwbergsvalley in the Western Cape during the 18th and 19th century - Breytenbach, Marius Ebersohn (Department of Archaeology, 2018)
The farm Blaauwbergsvalley, situated on the Cape west coast just outside Cape Town, has been identified as the place where a field hospital was set up for the casualties from the Battle of Blaauwberg in 1806. The significance of the site, however, extends beyond this specific event and includes a longer sequence of colonial and precolonial occupation. This is because a vlei provided a continuous supply of fresh but brackish water. Documentary evidence is discussed that draws attention to the growing importance of the western Cape Slagtersveld from 1652 as a region for livestock production to supply that VOC and its trading fleet. This contrasts with the Stellenbosch and Franschoek areas that developed more broadly around agriculture. More specifically, while it is likely that Blaauwbergsvalley, was a node in the 18th century development of this livestock landscape, it only formally appears in the documentary record from the late 18th century. The documents suggest that Blaauwbergsvalley, never fully functioned as a livestock farm but that it served as an outspan and a place that served the wider region and the flow of livestock and goods between the Table Valley settlement and the western Cape interior. The documented character of Blaauwbergsvalley is cautiously assessed against the archaeology of one area associated with the vlei. It is suggested that the archaeological evidence supports the transient, outspan function of Blaauwbergsvalley particularly in the period between 1800 and 1837 and that its material signature is not typical of other farms and werfs in the region. This needs to be assessed through future research.